392 Adjuvants for the potentiation of the activity of β-lactam antibiotics against methicillin-resistant Staphylococcus aureus - Caitlyn Thomas; Caitlyn A Thomas; Choon Kim; Amr M. El-Araby; Biruk T. Birhanu; Shahriar Mobashery; Mayland Chang (Journal of Clinical and Translational Science)
Objectives/Goals: Methicillin-resistant Staphylococcus aureus (MRSA) is a human bacterial pathogen and is classified as a serious threat. MRSA has become resistant to most B-lactam antibiotics (penicillins and cephalosporins). The goal of this study is to identify an antibiotic adjuvant capable of resurrecting B-lactams for the treatment of MRSA infections. Methods/Study Population: A fluorescence-reporter assay was used to screen a compound library. Minimum-inhibitory concentrations were assessed for the compounds against various MSSA and MRSA strains. A common resistance mechanism to B-lactams by MRSA is by the function of the bla operon. One gene in this operon encodes for a B-lactam sensor/signal transducer protein BlaR, the primary target of this study. Inhibition of BlaR by compound 1 (best potentiator of oxacillin) was studied by nano-differential scanning fluorimetry (nanoDSF), surface plasmon resonance (SPR), scanning electron microscopy (SEM), and time-kill assays. Results/Anticipated Results: We identified 80 compound hits from a 1,974-compound NCI library. Twenty-four compounds showed potentiating ability (2- to 4,096-fold decrease in MIC for oxacillin). Seven compounds exhibited melting temperature shifts by nanoDSF of BlaR, indicating binding. SPR determined compound 1 has a binding affinity of 31 micromolar to BlaR-SD. SEM images showed disruption in the S. aureus cell wall on exposure to compound 1 and oxacillin. S. aureus N315 showed 3-log reduction in bacterial count treated with a mixture of compound 1 and oxacillin. Discussion/Significance of Impact: Compound 1 targets BlaR-SD, which restores S. aureus susceptibility to treatment by oxacillin. There are currently few antibiotics available in the clinic capable of treating MRSA infections. The combination hold promise of a treatment option for MRSA.